Cross-economy dynamics in energy productivity: Evidence from 47 economies over the period 2000-2015 - Yang Liu; Sheng Zhong (Asian Development Bank Institute (ADBI), 2021)
This study investigates the long-run cross-economy dynamics in energy productivity across the world. We construct a data set comprising value-added and energy use data on 18 productive sectors in 47 economies over the period 2000-2015. First, we analyze the cross-economy distribution of energy productivity. Compared to 2000, this distribution shifted more towards the world average level in 2015. By using an index decomposition approach, we disentangle energy efficiency effect and economic structure effect as key determinants of the overall energy productivity improvement. Our results show that energy productivity progress is to a large extent driven by technological change but offset by economic structural change. Second, we explore the long-run distribution of energy productivity. Diverse patterns of energy productivity changes across these economies contradict the implicit assumption of standard convergence analysis. To address this issue, we adopt the Markov chain transition matrix. In a long-run steady state, around 64% of sample economies upgrade towards the upper end of the whole distribution, with their energy productivity performing better than the world average. Around 18% of sample economies remain at a level lower than the world average. The results suggest the persistent gap in energy efficiency across economies.
Keywords: Q01; Q56; O13; 330; energy productivity; decomposition; transition matrix; convergence